The effect of biomass ratio and CaO/Si catalyst on hydrogen production from corncob–wood pellet gasification - Purbo Suwandono; Widya Wijayanti; Nova Risdiyanto Ismail; Dzulfikar Johan Akbar; Wisnu Setyo Catur Pambudi (Jurnal Polimesin, 2025)
Biomass co-gasification combined with catalytic upgrading offers a promising pathway for enhancing hydrogen-rich syngas production. This study investigates co-gasification of corncob and wood pellets in an updraft fixed-bed reactor, integrated with ex-situ CaO/Si catalytic upgrading. Nine experimental runs were conducted by varying the corncob: pellet ratio (1:1–3:1), catalyst loading (6–10 wt% of 80 g biomass), and CaO/Si ratio (1:1–3:1), while reactor geometry, inlet air speed (10 m/s), and run duration (1500 s) were kept constant. The product gas was routed through an ex-situ catalyst bed, cooled in a condenser, and then analyzed using calibrated MQ sensors (H₂, CH₄, CO, CO₂). Gas composition was monitored using calibrated MQ sensors to provide comparative trends among operating conditions. The best performance was observed in Run 7 (50:50 biomass ratio, 10 wt% catalyst, CaO/Si = 2:1), achieving peak H₂ at 8000 ppm and CH₄ at 46,000 ppm, while CO₂ decreased to 16,000 ppm compared with several other runs. This outcome was consistent with CO₂ sorption by CaO, which can shift reactions toward higher H₂ formation (e.g., via the WGS equilibrium), and was supported by downstream upgrading reactions in the hot-gas line. The results suggest that combining biomass blending with ex-situ CaO/Si upgrading can improve the characteristics of hydrogen-enriched syngas within the investigated operating range.Biomass co-gasification combined with catalytic upgrading offers a promising pathway for enhancing hydrogen-rich syngas production. This study investigates co-gasification of corncob and wood pellets in an updraft fixed-bed reactor, integrated with ex-situ CaO/Si catalytic upgrading. Nine experimental runs were conducted by varying the corncob: pellet ratio (1:1–3:1), catalyst loading (6–10 wt% of 80 g biomass), and CaO/Si ratio (1:1–3:1), while reactor geometry, inlet air speed (10 m/s), and run duration (1500 s) were kept constant. The product gas was routed through an ex-situ catalyst bed, cooled in a condenser, and then analyzed using calibrated MQ sensors (H₂, CH₄, CO, CO₂). Gas composition was monitored using calibrated MQ sensors to provide comparative trends among operating conditions. The best performance was observed in Run 7 (50:50 biomass ratio, 10 wt% catalyst, CaO/Si = 2:1), achieving peak H₂ at 8000 ppm and CH₄ at 46,000 ppm, while CO₂ decreased to 16,000 ppm compared with several other runs. This outcome was consistent with CO₂ sorption by CaO, which can shift reactions toward higher H₂ formation (e.g., via the WGS equilibrium), and was supported by downstream upgrading reactions in the hot-gas line. The results suggest that combining biomass blending with ex-situ CaO/Si upgrading can improve the characteristics of hydrogen-enriched syngas within the investigated operating range.